PELATIHAN PERBANYAKAN TANAMAN MULTI-PURPOSE TREE SPECIES MELALUI TEKNIK OKULASI, SAMBUNG PUCUK, DAN STEK KEPADA SISWA SMKN PERTANIAN PEMBANGUNAN AMBON - Andjela Sahupala; Marthini Kristina Lesilolo; Jimmy Johanson Fransz; Irwanto Irwanto (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aimed to improve the knowledge and skills of students of SMKN Pertanian Pembangunan Ambon in vegetative propagation techniques for Multi-Purpose Tree Species (MPTS) plants, including budding, grafting, and cuttings. The participants consisted of 20 students from SMKN Pertanian Pembangunan Ambon. The implementation methods included interactive lectures, demonstrations of propagation techniques, direct field practice, as well as discussions and evaluations. The activity was conducted at the Greenhouse of the Faculty of Agriculture, Universitas Pattimura on November 25–26, 2026. The evaluation results showed a 60% increase in students’ knowledge and a 65% improvement in practical skills compared to before the training. All participants were able to independently practice the cutting technique, while more than 85% of participants successfully mastered budding and grafting techniques. The participant satisfaction level with this activity reached 90%. This activity is expected to support the development of students’ competencies in horticultural agribusiness and prepare them to enter the workforce or become entrepreneurs in the agricultural sector.